Zabiegi polskiej dyplomacji o międzynarodowe uznanie granicy ryskiej - Pisuliński, Jan (1968– ) (Instytut Historii PAN, 2024)
The article discusses the steps Polish diplomacy took to obtain recognition of the eastern border delineated by the Treaty of Riga by the powers represented in the Council of Ambassadors. The first efforts were made even before the signing of peace in February 1921. The article presents the actions of subsequent foreign ministers, Eustachy Sapieha, Konstanty Skirmunt, Gabriel Narutowicz, and Aleksander Skrzyński, culminating in a decision favourable to Poland in March 1923.
p. 5-241
Summary in English.
Keywords: Conference of Ambassadors; Europe - politics and government - 1918-1945; Treaty of Riga (1921); Genoa Conference, 1922; Poland - borders - 1900-1945; Sapieha, Eustachy Kajetan (1881-1963); Skirmunt, Konstanty (1866-1949); Narutowicz, Gabriel (1865-1922); Skrzyński, Aleksander (1882-1931)